Papillomas and carcinomas of the choroid plexus: histological and immunohistochemical studies and comparison with normal fetal choroid plexus - Ana Silvia Carvalho de Menezes Barreto; José Vassallo; Luciano de Souza Queiroz (Arquivos de Neuro-Psiquiatria)
BACKGROUND: Choroid plexus tumors are rare. Results on immunohistochemical features are scanty and controversial even regarding normal plexus. METHOD: Thirteen cases of choroid plexus tumors and five samples of normal fetal choroid plexus were submitted to immunohistochemical study using a panel of epithelial, neuronal and stromal markers. RESULTS/CONCLUSIONS: Relevant histological findings were presence of clear cells in 3/5 papillomas (PP) and 7/8 carcinomas (CA) and all 5 fetal plexuses; rhabdoid cells, desmoplasia and vascular proliferation were found respectively in 3, 4 and 5 cases out of 6 poorly differentiated CA and were absent in PP and well differentiated CA. Pancytokeratin AE1/AE3 was strongly positive in all 13 cases, even in the undifferentiated component of poorly differentiated CA, where reactivity was focal in 3 and diffuse in 3 cases. Low molecular weight cytokeratin (35bH11) was not expressed in any of the 8 CA, but was present in all 5 PP. In 4 of 6 poorly differentiated CA there was reactivity for smooth muscle actin (1A4) in 10 to 30% of the cells. This was true also for one case lacking rhabdoid cells. Laminin was undetectable in all 6 cases of poorly differentiated CA but was present in 4 PP and 2 well differentiated CA. All 5 fetal plexuses expressed GFAP.